Bibliometric and thematic evaluation of Education journals included in the Scimago Journal Rank - Gregorio-Chaviano, Orlando (2021)
The objective of this research is to analyze the Colombian education journals included in the Scimago Journal Rank (SJR), using bibliometric indicators and editorial quality criteria, which allow to know trends and behaviors both from a bibliometric and management perspective. A search was made of all the information registered by each journal in the Scopus database and after a cleaning process, production, citation and network indicators were obtained, as well as the analysis of inbreeding, attractiveness and other variables.  The main results were low average number of citations per document and the SJR (prestige indicator), 10% self-citation and journals with more than 20% endogamy, in addition to a high international participation in the contributions. With respect to the citations received, these come from journals in the same area and distributed in the different quartiles. In general, the methodology used provides elements on the status and evolution of the selected journals, which can also be applied to the study of others journals.